Integrated Transcriptomic and Proteomic Analyses Uncover the Regulatory Mechanisms of Myricaria laxiflora Under Flooding Stress - Li, Linbao; Huang, Guiyun; Xiang, Weibo; Zhu, Haofei; Zhang, Haibo; Zhang, Jun; Ding, Zehong; Liu, Jihong; Wu, Di (Frontiers in Plant Science, 2022)
Flooding is one of the major environmental stresses that severely influence plant survival and development worldwide. However, the regulatory mechanisms underlying flooding stress remain largely unknown in Myricaria laxiflora, an endangered plant mainly distributed in the flood zone of the Yangtze River, China. In this work, transcriptome and proteome were performed in parallel in roots of M. laxiflora during nine time-points under the flooding and post-flooding recovery treatments. Overall, highly dynamic and stage-specific expression profiles of genes/proteins were observed during flooding and post-flooding recovery treatment. Genes related to auxin, cell wall, calcium signaling, and MAP kinase signaling were greatly down-regulated exclusively at the transcriptomic level during the early stages of flooding. Glycolysis and major CHO metabolism genes, which were regulated at the transcriptomic and/or proteomic levels with low expression correlations, mainly functioned during the late stages of flooding. Genes involved in ROS scavenging, mitochondrial metabolism, and development were also regulated exclusively at the transcriptomic level, but their expression levels were highly up-regulated upon post-flooding recovery. Moreover, the comprehensive expression profiles of genes/proteins related to redox, hormones, and transcriptional factors were also investigated. Finally, the regulatory networks of M. laxiflora in response to flooding and post-flooding recovery were discussed. The findings deepen our understanding of the molecular mechanisms of flooding stress and shed light on the genes and pathways for the preservation of M. laxiflora and other endangered plants in the flood zone.